2021
DOI: 10.3389/fpsyg.2021.673597
|View full text |Cite
|
Sign up to set email alerts
|

Electrodermal Response to Mirror Exposure in Relation to Subjective Emotional Responses, Emotional Competences and Affectivity in Adolescent Girls With Restrictive Anorexia and Healthy Controls

Abstract: Objective: Body image disturbances and the attendant negative emotions are two of the major clinical symptoms of eating disorders. The objective of the present experimental study was to shed more light on the degree of association or dissociation between the physiological and emotional response to mirror exposure in patients with restrictive mental anorexia, and on the relationships between the physiological response and characteristics connected with emotional processing.Materials and Methods: Thirty adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Differently, AN participants primarily demonstrated lower EDA than healthy samples (Clarke et al, 2016;Knejzlíková et al, 2021;Palomba et al, 2017), except when presented with body-related words or with food-related stimuli after consuming food (Soussignan et al, 2010;Steward et al, 2022). Knejzlíková et al (2021) observed higher EDA variability in AN compared to HC, but no differences during a mirror exposure. Patients with BN showed lower EDA than subclinical restrictive eaters but did not differ from controls (Tuschen-Caffier & Vögele, 1999).…”
Section: Electrodermal Activitymentioning
confidence: 72%
“…Differently, AN participants primarily demonstrated lower EDA than healthy samples (Clarke et al, 2016;Knejzlíková et al, 2021;Palomba et al, 2017), except when presented with body-related words or with food-related stimuli after consuming food (Soussignan et al, 2010;Steward et al, 2022). Knejzlíková et al (2021) observed higher EDA variability in AN compared to HC, but no differences during a mirror exposure. Patients with BN showed lower EDA than subclinical restrictive eaters but did not differ from controls (Tuschen-Caffier & Vögele, 1999).…”
Section: Electrodermal Activitymentioning
confidence: 72%
“…These studies, however, generally used longer measurement intervals [ 31 ]. Other psychophysiological measures, such as skin conductance reactivity, were also reported to be blunted in AN under various conditions [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also suggest blunted psychophysiological responses to emotional content in AN, e.g., attenuated startle reflex reactivity to fear-inducing material [ 17 ], but similar peripheral physiological responses to emotion-eliciting film clips as in healthy women [ 18 ]. Adolescent AN patients who performed a body-related task (mirror exposure) showed a dissociation between psychophysiological reactivity (no differences in skin conductance responses compared to typical developing girls) and subjective responses (more negative emotion ratings) [ 19 ]. Similarly, in patients with AN, when looking at their own and other body silhouettes, there was no correlation between another psychophysiological measure—the pupil psychosensory reflex—and self-reported emotional arousal.…”
Section: Introductionmentioning
confidence: 99%
“…Among body exposure treatments, the two most widely used and verified modalities are guided exposure (the person is told which parts of the body to pay attention to: “beautiful” or “ugly” parts) and pure exposure (the person must pay attention to their whole body, with no guidance as to which parts to attend to). The literature finds conflicting results on whether guided exposure treatments show a greater reduction in BD, especially focusing on body parts considered “negative/ugly” [ 19 , 20 ] compared to those without such guidance [ 16 , 29 , 30 ]. However, one fact that has been widely established is that both can be clinically effective in improving BD, body checking/avoidance behaviors, and patients’ moods [ 16 , 31 ].…”
Section: Introductionmentioning
confidence: 99%